Analysis of the prediction and evolution process of waterfilling in closed coal mine goaf - Yanqing DING; Renhao PANG; Jing QIAN; Lihong DUAN; Taisen CHEN (Meitan xuebao)
After coal mine closure, the groundwater level recovers, while the water accumulation process in goaf areas has rarely been studied. Taking Xuzhou Sanhejian closed coal mine as an example. Based on mine closure reports and borehole data, combined with 3D contour maps of coal seam floor elevations, the water accumulation pathways in goaf areas were identified. The mine water accumulation volume was predicted by mining-induced space method through separate calculations for different coal seams and levels. Water inflow rates at various levels after mine closure were determined using hydraulic theory and related principles, revealing the evolutionary process of water accumulation in abandoned mine goaf. Research shows: According to 3D coal seam floor morphology, mine water first flows to deep goaf areas and roadways in the north and south wings, then passes through central goaf areas in the east and west wing edge zones, and finally converges to shallow goaf areas near Longgu anticline and Zhangzhuang fault. The total accumulated water volume in Sanhejian closed mine is 9.88×106 m3, including 9.35×106 m3 calculated by mining-induced space method (7.86×106 m3 in goaf areas and 1.49×106 m3 in abandoned roadway systems), with 0.53×106 m3 from other water storage spaces. As water level rises, water inflow rate gradually decreases, reaching the minimum value of approximately 134.81 m3/h at −350− −400 m elevation. The groundwater recovery process reveals three phases: initial stage features small deep goaf capacity, high inflow rate and rapid accumulation; mid-stage shows increased goaf capacity, reduced inflow rate, and slowed rising speed with more roadways; final stage exhibits reduced shallow goaf capacity and accelerated water level rise. It is predicted that groundwater will recover to −350 m elevation after 2546 days of mine closure.